2021
DOI: 10.1177/14799731211015691
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of rehabilitation for individuals post-COVID to improve fatigue, breathlessness exercise capacity and cognition – A cohort study

Abstract: Individuals with lasting symptoms of COVID-19 should be offered a comprehensive recovery programme. 30 individuals (mean[SD] age 58[16]) that completed a 6 week, twice supervised rehabilitation programme demonstrated statistically significant improvements in exercise capacity, respiratory symptoms, fatigue and cognition. Participants improved by 112 m on the Incremental Shuttle Walking Test and 544 seconds on the Endurance Shuttle Walking Test. There were no serious adverse events recorded, and there were no d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
261
3
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(288 citation statements)
references
References 6 publications
10
261
3
14
Order By: Relevance
“…To date, it remains unknown which treatment strategies are effective to improve fatigue in patients with long COVID. Several treatment strategies for fatigue are proposed based upon knowledge from the fast-growing evidence regarding COVID-19 and other pathologies, such as multidisciplinary rehabilitation, energy conservation techniques, pacing, cognitive behavioral therapy, graded exercise therapy, or physical training [ 25 , 54 , 60 - 65 ]. Future research needs to provide evidence regarding underlying pathways, evaluate the effectiveness of existing treatment strategies, and identify susceptible candidates, as it is expected that not everyone will benefit from the same treatment strategy due to the multifactorial nature of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it remains unknown which treatment strategies are effective to improve fatigue in patients with long COVID. Several treatment strategies for fatigue are proposed based upon knowledge from the fast-growing evidence regarding COVID-19 and other pathologies, such as multidisciplinary rehabilitation, energy conservation techniques, pacing, cognitive behavioral therapy, graded exercise therapy, or physical training [ 25 , 54 , 60 - 65 ]. Future research needs to provide evidence regarding underlying pathways, evaluate the effectiveness of existing treatment strategies, and identify susceptible candidates, as it is expected that not everyone will benefit from the same treatment strategy due to the multifactorial nature of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…These uncertainties, and the fact that little data exists to date, mean treatment may require a multidisciplinary care pathway [86,87]. Limited reporting of interventions with overinterpretations regarding safety [21] do not serve the long COVID research, allied health professional, nor patient community. It is essential that future clinical trials (including pilot/feasibility studies) report modifications, symptom exacerbation and other adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the identification of PEM in people living with long COVID has been driven by one remarkable patient-led effort that asked participants to identify PEM based on a definition of PEM [8,9]. However, to date, preliminary studies exploring progressive exercise have not reported any measure of PEM at enrollment, nor reported monitoring tolerability or symptom exacerbation in response to exertion [21,22]. This may be because the presence of PEM in people living with long COVID has not been clearly identified using self-report tools that are validated in people with ME/CFS.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that many non-critically ill hospitalized COVID-19 survivors’ ability to resume pre-COVID-19 roles and responsibilities were negatively impacted at least in the short, and possibly, long term 33 . Other studies have found that impaired functional status extended well beyond hospital discharge as patients were reporting persistent symptoms that impact their functional abilities six months after disease onset 29 31 , 34 36 .…”
Section: Discussionmentioning
confidence: 78%